The Translator as a Mediator in the Dialogue of Literatures - Li, Yuanchun; Latfullina, Landysh G.; Nagumanova, Elvira F.; Khabibullina, Alsu Z. (Journal of History Culture and Art Research, 2017)
The article raises the issue of translating the works of national literatures through an intermediate language since most of the works of the peoples of Russia find their readers in the world thanks to the Russian language. The urgency of this problem is obvious in modern conditions when the interest in Turkic-speaking literature is growing, and many Russian poets, like in the Soviet era, see themselves as the translators from national languages. On the example of the translation of the poem «tɵshtǝgechǝ bu kɵn – sǝer Һǝm iat …» (“the day is like a dream”) of the contemporary poetess Yulduz Minnullina both the strengths and the weaknesses of the modern translation school are considered. The word for word translation can lead to the unification of differences between literatures when the dominant language (the Russian language) imposes certain aesthetic principles on the original text. The most important aspect of the topic of interest is the consideration of the role of interlinear translation in the establishment of interliterary dialogue. Through interlinear translation a foreign work, endowed with its special world of ideas, images, national and artistic traditions, serves as the basis for dialogical relations that are indispensable for both the Russian-speaking reader who discovers the “other” literature, and the very work that is included in the dialogue in the “large time”. At the same time, the elimination of differences between literatures occurs when the translator, through the Russian language, by means of line-by-line translation, introduces the features of his own consciousness into a foreign work. In this case, the translation simplifies the content of the literature, equalizes the artistic merits, thereby projecting the life of the work onto communication, rather than dialogue.